2017
DOI: 10.1108/ijccsm-06-2017-0140
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem services in adaptation projects in West Africa

Abstract: Purpose The purpose of this paper is to assess the extent to which adaptation projects have incorporated ecosystem services, as well as their redesigning options. The projects selected are listed under National Adaptation Programme of Action in West African region. Design/methodology/approach A desktop survey approach was used to review 168 projects from 13 countries across West Africa. The projects were categorized and analyzed according to their adaptation goal, thematic focus, their implementation duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The study employed the Millennium Ecosystem Assessment (2005) categorization of ecosystem services (provisioning, support, regulatory, and cultural) to establish various ecosystem services derived from agroforestry technologies. This review found that most agroforestry technologies generate more than one category and type of ecosystem services in line with Muthee et al. (2018) , who argue that agroforestry is multifunctioning and multiple beneficial in supporting livelihoods and ecological functioning.…”
Section: Resultsmentioning
confidence: 62%
“…The study employed the Millennium Ecosystem Assessment (2005) categorization of ecosystem services (provisioning, support, regulatory, and cultural) to establish various ecosystem services derived from agroforestry technologies. This review found that most agroforestry technologies generate more than one category and type of ecosystem services in line with Muthee et al. (2018) , who argue that agroforestry is multifunctioning and multiple beneficial in supporting livelihoods and ecological functioning.…”
Section: Resultsmentioning
confidence: 62%
“…However, the current trends in tropical deforestation and forests degradation have jeopardized the global efforts to curb climate change and its adverse effects on ecosystems and livelihoods. Studies such as Muthee et al (2018Muthee et al ( , 2021 note anthropogenic and natural factors, such as ecosystems conversion to support livelihoods, unsustainable natural resources extraction, and wildfires, as some of the key drivers behind tropical deforestation and forest degradation.…”
Section: Brief Background On Tropical Forests Conservation and Climate Risks Managementmentioning
confidence: 99%
“…They have minimal consideration of the interlinkages among different sectors and the existing cross-cutting relationships among the three domains [5]. Consequently, the net effect has been the promotion of one system (such as agriculture for food) at the expense of the other interlinked segments such as water, energy, and livelihoods, as Muthee et al [16] argued. At the resource use and decision-making level, Karnib [17] noted that water, energy, and food are viewed independently in most countries, with minimal cross-cutting policies and strategies.…”
Section: Scenario Descriptionmentioning
confidence: 99%